High Rank Coal Pore Fracture Structure and its Impact on Reservoir Characteristics in the Southern Qinshui Basin - Ji, Changjiang; Li, Guofu; Hao, Haijin; Song, Zhimin; Guo, Dingding (Frontiers in Earth Science, 2022)
Although the southern Qinshui Basin is the most successful area for coalbed methane (CBM) development in China, the production of CBM wells in different blocks in the area is significantly different. One of the key reasons is the difference in pore structure in various-ranked coal. In this study, No. 3 coal seam of Sihe and Zhaozhuang blocks in southern Qinshui Basin was selected as the research object to investigate the high rank coal pore fracture structure and its impact on reservoir characteristics. Mercury intrusion porosimetry (MIP), low-temperature liquid nitrogen adsorption (LTN2A), scanning electron microscopy (SEM), and isothermal adsorption tests were conducted. The results show that the Sihe No.3 coal seam was mainly composed of open cylindrical and flat pores with a high proportion of transition pores (10–100 nm), large specific surface area, good connectivity, strong adsorption capacity, high gas content, and reservoir energy. Zhaozhuang No.3 coal had high proportion of mesopores (100–1,000 nm), small specific surface area, poor pores connectivity, weak adsorption capacity, poor gas content, low reservoir energy, and critical desorption pressure. The proportion of cylindrical pores, parallel plate pores, and wedge-shaped pores closed at one end was high. The anomalies in pore morphology and pore structure characteristics of coal reservoir were the main factors that caused variation in gas production of No.3 coal seam in Sihe and Zhaozhuang blocks.